Central chemoreception in wakefulness and sleep: evidence for a distributed network and a role for orexin - Nattie, Eugene (American Physiological Society, 2010)
This minireview examines data showing the locations of central chemoreceptor sites as identified by the presence of ventilatory responses to focal, mild acidification produced in unanesthetized animals in vivo, how the site-specific responses vary by arousal state, and what the emerging role of orexin might be in this state-dependent central chemoreceptor system. We comment on the organization of this distributed central chemoreceptor system and suggest that interactions among sites are synergistic and not additive, which is an important aspect of its normal function.